SOSIALISASI PERAN KOPERASI SIMPAN PINJAM CU DHARMA BAKTI TERHADAP PEMBERDAYAAN MASYARAKAT - Hasim Asari; Irene Surat Juan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Socialization is a lifelong process that is concerned with how individuals learn things, such as social norms and values. Socializing requires the activeness of each individual to want to join in a community or community group. This activity can be obtained through the process of learning and adjustment. Therefore, individuals must actively learn from their surroundings. Community empowerment activities are one of the most effective activities in the context of self-reliance and empowerment of the community. These activities can be done anywhere, anytime and by anyone. Basically community empowerment activities are aimed at those who are economically disadvantaged and not yet independent. Through cooperatives, young people should spearhead the Indonesian nation's entrepreneurship development movement so that every community has entrepreneurial skills. Entrepreneurial skills are ultimately expected to free the Indonesian nation from the shackles of poverty. The purpose of the researchers to examine the socialization of the role of community empowerment itself is so that we can find out the role of savings and loan cooperatives in empowering Indonesian society. This study uses qualitative methods, namely observation and interviews in order to see the extent to which savings and loan cooperatives have succeeded in empowering the community's economy. The results of the study show that the Dharma Bakti CU savings and loan cooperative has a very large role in participating and supporting the development and development of the community's economy. The empowerment program provided by the cooperative to the community is able to help them develop their business.